Comparison and cost analysis of three protocols for mobilization and apheresis of haematopoietic progenitor cells. Issue 4 (28th February 2019) - López‐Castaño, Francisco; Manresa, Pablo; Díaz, Vanesa; Arranz, Eva; López, Javier; Pérez, María; Alda, Olga; Hernández, Luis
Abstract: Introduction: Autologous bone marrow transplantation is a component of the malignant hemopathy therapy. The preferred mobilization and collection method is apheresis. The aim of this study is to compare three protocols analyzing the effect of plerixafor, higher dose of G‐CSF and large volume leukapheresis (LVL). Materials and methods: A retrospective cohort study including 119 patients referred for mobilization. Three protocols were compared: (a) G‐CSF 10 μg/kg/day subcutaneous (sc) × 4 days mobilizing 1 to 1.5 blood volumes. (b) G‐CSF 10 μg/kg/day sc × 4 days + plerixafor 0.24 mg/kg/day sc preventively or as a rescue agent mobilizing 1 to 1.5 blood volumes. (c) G‐CSF 20 μg/kg/day sc × 4 days ± plerixafor 0.24 mg/kg/day sc preventively or as a rescue agent mobilizing 3 to 4 blood volumes. Results: The average number of days of apheresis was reduced to 1.37 with protocol 3. The average cost per patient was reduced by 67% compared with protocol 2 and increased by only 5% compared with protocol 1, reducing the failure rate to 0%. Conclusion: Adding preemptive or rescue plerixafor (protocol 2) to G‐CSF 10 μg/kg/day alone (protocol 1) did not improve the days of apheresis nor the number of CD34+ cells collected but had higher cost and failure rate. Using LVL, plerixafor and G‐CSF 20 μg/kg/day (protocol 3) decreased the number of sessions to 1.37, reduced the failure rate to 0% and led to a significant increase in the number of CD34+ cells collected without toxicity and with a similar cost to protocol 1.